Work Design: Characterization of the phenomenon and analysis of its relationships - Nana Caroline Cunha de Jesus; Antonio Virgílio Bittencourt Bastos; Carolina Villa Nova Aguiar (Revista Psicologia)
The objective of this study was to characterize the organization of work in a public university of higher education in Northeastern Brazil, exploring the relationships between the different dimensions and subdimensions of the model proposed by Morgeson and Humphrey. In total, 691 technical-administrative staff participated in this cross-sectional, quantitative study. The WDQ (Work Design Questionnaire) version in the process of validation in Brazil was used. Descriptive (mean, standard deviation, and frequency distribution) and inferential (Pearson’s correlation and Student’s t-test) analyses were conducted. The results revealed a work design that links richer levels of task scope and use of knowledge with more precarious contextual conditions. Since this is the first study using the Morgeson and Humphrey model in Brazil and at this institution, further research is needed to broaden the understanding of how work is organized in singular institutions such as universities.